ImiFlex Evaluation at Two Kansas Locations in Igrowth Grain Sorghum - P. W. Geier; R. S. Currie; S. H. Lancaster; C. M. Weber (Kansas Agricultural Experiment Station Research Reports, 2023)
Herbicide-tolerant grain sorghums, such as Igrowth (imidazolinone-resistant) hybrids were recently commercialized in Kansas. Even though the active ingredient of the herbicide associated with these systems, imazamox, is used in other crops, data are needed to define best practices for use in grain sorghum. The objective of these studies was to evaluate ImiFlex (imazamox) herbicide in Igrowth grain sorghum at two Kansas locations in 2022. ImiFlex applied postemergence provided 93% volunteer corn control, and 90 to 95% johnsongrass control regardless of application timing at Garden City. At Manhattan, ImiFlex controlled Palmer amaranth 90 to 99%. Early season grain sorghum injury was 13% or less, and generally did not persist. Grain yields from ImiFlex-treated sorghum were significantly greater than yields from the nontreated controls and from treatments that did not contain ImiFlex.
Keywords: Herbicide resistance; grain sorghum; volunteer corn; johnsongrass